The antimicrobial peptide cathelicidin modulates Clostridium difficile-associated colitis and toxin A-mediated enteritis in mice. Issue 9 (3rd July 2012) - Hing, Tressia C; Ho, Samantha; Shih, David Q; Ichikawa, Ryan; Cheng, Michelle; Chen, Jeremy; Chen, Xinhua; Law, Ivy; Najarian, Robert; Kelly, Ciaran P; Gallo, Richard L; Targan, Stephan R; et al.
Abstract : Background: Clostridium difficile mediates intestinal inflammation by releasing toxin A (TxA), a potent enterotoxin. Cathelicidins ( Camp as gene name, LL-37 peptide in humans and mCRAMP peptide in mice) are antibacterial peptides that also posses anti-inflammatory properties. Objectives: To determine the role of cathelicidins in models of Clostridium difficile infection and TxA-mediated ileal inflammation and cultured human primary monocytes. Design: Wild-type (WT) and mCRAMP-deficient ( Camp −/− ) mice were treated with an antibiotic mixture and infected orally with C difficile . Some mice were intracolonically given mCRAMP daily for 3 days. Ileal loops were also prepared in WT mice and treated with either saline or TxA and incubated for 4 h, while some TxA-treated loops were injected with mCRAMP. Results: Intracolonic mCRAMP administration to C difficile -infected WT mice showed significantly reduced colonic histology damage, apoptosis, tissue myeloperoxidase (MPO) and tumour necrosis factor (TNF)α levels. Ileal mCRAMP treatment also significantly reduced histology damage, tissue apoptosis, MPO and TNFα levels in TxA-exposed ileal loops. WT and Camp −/− mice exhibited similar intestinal responses in both models, implying that C difficile /TxA-induced endogenous cathelicidin may be insufficient to modulate C difficile /TxA-mediated intestinal inflammation. Both LL-37 and mCRAMP also significantly reduced TxA-induced TNFα secretion via inhibition of NF-κB phosphorylation. Endogenous cathelicidin failed to control C difficile and/or toxin A-mediated inflammation and even intestinal cathelicidin expression was increased in humans and mice. Conclusion: Exogenous cathelicidin modulates C difficile colitis by inhibiting TxA-associated intestinal inflammation. Cathelicidin administration may be a new anti-inflammatory treatment for C difficile toxin-associated disease.